Impacts of Self-Regulated Strategy Development-Based Revision Instruction on English-as-a-Foreign-Language Students' Self-Efficacy for Text Revision: A Mixed-Methods Study - Chen, Jing; Zhang, Lawrence Jun; Wang, Xiao; Zhang, Tingting (Frontiers in Psychology, 2021)
This mixed-methods study investigated the effects of the self-regulated strategy development (SRSD) model on students’ self-efficacy for text revision in English-as-a-foreign-language (EFL) writing at the tertiary level. An SRSD treatment group and a comparison group were involved in this quasi-experimental design research. Both groups completed a self-efficacy scale before and after the instruction and six SRSD-trained students participated in pre- and posttest interviews. The quantitative analyses did not detect any significant differences between groups, suggesting that the SRSD instruction did not influence participants’ self-efficacy for text revision. The qualitative findings provided insights into the quantitative results. The interview data indicated that the interviewees might have overestimated their revision abilities before instruction and, with the relatively more accurate estimation of their abilities resulting from receiving the SRSD instruction, the over-time comparison of their responses to the self-efficacy scale did not reveal any statistically significant changes. Our findings suggest that students might have recorded evidence of closer calibration between judgements of their revision abilities and their actual performance after SRSD instruction. The implications of the findings were discussed and directions for further studies provided.